Physical and aerodynamic properties of date palm pollen grains - Mohamed M. IBRAHIM; Mohamed GHONIMY; Eid ABD EL RAHMAN (Acta Agriculturae Slovenica)
The present study was designed to determine the effect of four moisture content levels (4, 5, 6, and 7 %) on the physical and aerodynamic properties of date palm pollen grain (DPP). The physical properties of DPP included pollen length (L), width (w), thickness (T), projected area (Ap), geometric mean diameter (dg), mass (m), sphericity (S), and bulk density (ρp). It was observed that the moisture content did not significantly influence the physical properties of the DPP. The aerodynamic properties of DPP included the terminal velocity (Vt), drag coefficient (Dc), drag force (Df), and Reynolds number (Re). The pollen Reynolds number (Re) is significant at different pollen grain moisture content, and regression models were developed in the form of polynomial and exponential relationships. Also, the 3rd order polynomial relationship was found between Re and Dc. The results showed that the average values of Vt, Dc, Df, and Re were about 0.6 m s-1, (0.38 to 0.45), 1.09E-11 N, and (0.29 to 0.42), respectively. The results of this study will be helpful in the performance of date palm pollination machines.